Buddhist fundraising (congdanbud) and gamification approach in improving students' cognitive skills - Desta Punda Rika; Ayu Andriyaningsih; Dedi Kundana (Universitas Sebelas Maret, 2025)
Cognitive skills are a crucial aspect of education because they directly relate to students' abilities to think critically, analyse information, understand concepts, and solve problems. These skills are the primary foundation for creating an effective, meaningful, and sustainable learning process. Improving cognitive skills not only impacts students' academic outcomes but also contributes to improving the overall quality of human resources. This is crucial in developing a generation capable of adapting and contributing to the nation's future progress. This study aims to determine the effect of the traditional Buddhist congklak game and a gamification approach on the cognitive skills of students at the Sakyamuni Buddhist Sunday School (BSS). The method used was a quantitative survey. The research instrument was a Likert-scale questionnaire distributed to the entire population of 32 students, who also served as the sample. Data analysis employed multiple linear regression using SPSS version 27. The study results indicate a positive and significant influence between the Buddhist congklak game and the gamification approach on improving students' cognitive skills, with a contribution of 83.8%. Meanwhile, the remaining 16.2% is influenced by other factors not examined in this study. These findings indicate that the application of Buddhist-based learning methods combined with a fun approach such as gamification is very effective in improving students' cognitive abilities in religious educational environments. Therefore, this approach deserves further development at various levels of education, both formal and non-formal, to create a fun, relevant, and transformative learning process to produce a superior generation with character according to Buddhist moral values in a holistic and sustainable manner today.